Keanekaragaman Tumbuhan Berdasarkan Morfologi Polen dan Spora dari Sedimen Telaga Warna Dieng, Kabupaten Wonosobo, Jawa Tengah - Azizah, Nurrahmah; Suedy, Sri Widodo Agung; Prihastanti, Erma (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
Pollen and spore may be used to identify the name of plants because on pollen and spore there is an outter wall, called exine, which have specific structure and sculpture. This specific morphology of pollen and spore may be easily identified, therefore the name of plant itself may be known directly. The aim of this research is to find out the various of pollen and spore morphology of Telaga Warna sediment and the name of plant itself may be known,moreover the plant diversity and the plant which is dominant around Telaga Warna may be known as well. This research had been conducted with fetched the sediment sample from the edge of Telaga Warna, Dieng, preparation of sample were using acetolysis method, and finally make microscopic preparation. Pollen and spore observed by some parameters: shape, size, polarity, symmetry, aperture, and sculpture. The information, furthermore, analyzed by making description of pollen and spore morphology and quantitative data. The result of this research reaveal that there are 34 kind of plants from pollen and spore observation. The amount of Pteridophytes is 53%, Non-Arboreal Pollen (NAP) is 29%, and Arboreal Pollen (AP) is 18%. The plant which dominant around Telaga Warna is Polypodiaceae, with the value of dominance index is 5,66. Its spore morphology has trilete aperture, heteropolar, bilateral symetry, and the sculpture is psilate. The average of plant diversity temporally in Telaga Warna is low, with the average value of diversity index is 1,56, however the alteration of vegetation temporally in Telaga Warna is stable dynamics. Â Keywords: morphology, pollen, spore, telaga warna